COMPARISON BETWEEN PAPER-BASED AND WEB- BASED TEST IN THE CLINICAL SKILLS LABORATORY OF UNDERGRADUATE STUDENTS - Doni Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: E-Learning or web-based technology can be used to train undergraduate medical students' clinical reasoning skills. Currently, many learning methods are being developed using web-based environment to replace paper-based because they are more efficient in terms of paper usage and are flexible for a student in accessing materials. This study aims to explore student's working durationaccess time and scores upon the usage of webbased test, to compare students' scores to paper-based test scores, to explore the advantages anddisadvantages, and suggestions to improve the web-based learning method. Method: This study randomly enlisted 60 medical students of Universitas Gadjah Mada, Yogyakarta, Indonesia and divided them into web-based (n = 30) and paper- based test (n = 30) groups. Students answered 15 disaster management questions and completed a questionnaire. The scores and times needed to answer the questions were compared using the Mann-Whitney and Independent Sample tests. Results: The duration to answer in the web-based group was shorter than in paper- based group (p = 0.001), but the average scores difference was not significant (p = 0.169). In the web-based group, similar numbers of students accessed the website during and after working hours. Survey questionnaire results showed that most students realized the advantages of this program and gave appropriate suggestions. Conclusion: Practicing clinical reasoning skills using web-based learning method is more time-efficient compared to the paper-based test. Its high-accessibility improves the learning interest and motivation of the student, with an equal outcome to the paper-based test.